1976
DOI: 10.1104/pp.57.3.440
|View full text |Cite
|
Sign up to set email alerts
|

Action Spectrum between 260 and 800 Nanometers for the Photoinduction of Carotenoid Biosynthesis in Neurospora crassa

Abstract: An action spectrum for light-induced carotenoid biosynthesis in Neurospora crassa was determined in 4 to 20 nm steps from 260 to 800 nm. Four-day, dark-grown mycelial pads of N. crassa were exposed to varying amounts of monochromatic radiant energy and time. After a 48-hour incubation period at 6 C, carotenoid content was assayed spectrophotometrically in vivo. The action spectrum has maxima at 450 and 481 nm in the visible range and at 280 and 370 nm in the ultraviolet. A pigment synthesized by Neurospora who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…In N. crassa, biochemical studies of the carotenoid biosynthetic pathway were carried out using wc and al mutants (9 (4,26,30). In contrast to these results, phytochrome has been proposed to be a photoreceptor for photoinduced carotenogenesis in another fungus Verticiium agaricinum (29).…”
Section: Discussionmentioning
confidence: 99%
“…In N. crassa, biochemical studies of the carotenoid biosynthetic pathway were carried out using wc and al mutants (9 (4,26,30). In contrast to these results, phytochrome has been proposed to be a photoreceptor for photoinduced carotenogenesis in another fungus Verticiium agaricinum (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although light signal transduction pathways have been primarily studied in plants (Chen et al, 2004), the filamentous fungus Neurospora crassa has become a preferred eukaryotic model to investigate pathways inducible by blue light. Early biochemical and photobiology studies reported that Neurospora is responsive only to blue light (Sargent and Briggs, 1967;DeFabo et al, 1976). Genes encoding putative red light photoreceptors have been recently discovered in the Neurospora genome (Galagan et al, 2003;Borkovich et al, 2004), but deletion of these genes does not affect any known photoresponses, leaving their function uncertain (Froehlich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although action spectra should provide, within limits, a reasonable representation of the absorption spectrum of the photoreceptor pigment, an action spectrum is insufficient for distinguishing between potential photoreceptor pigments with very similar absorption spectra (1,3,13). Moreover, the absorption spectrum for the photoreceptor pigment may depend strongly on its environment, but this environment is an unknown as long as the identity of the photoreceptor pigment itself is unknown.…”
Section: Introductionmentioning
confidence: 99%